Analysis of bioactive compounds, organic acids, and genetic parameters of ten amazonian robusta cultivars - Tadeu, Hugo C. [UNESP]; Ximenes, Valdecir F. [UNESP]; Lopes, Maria T. G.; Espindula, Marcelo C.; Alves, Ana P. de C.; Borém, Flávio M. (FapUNIFESP (SciELO), 2024)
Coffea canephora beans are used for various industrial purposes, among which the use as soluble coffees stands out for producing beverages in blends with Coffea arabica. Due to the increase in demand, EMBRAPA launched ten monoclonal C. canephora cultivars, named Amazonian Robustas, adapted to the growing conditions of the Brazilian Amazon. However, the chemical composition of the beans of these cultivars is still little known. The present study aimed to estimate genetic parameters for the evaluated characteristics and determine the levels of bioactive compounds and organic acids in ten C. canephora cultivars. The experiment was set in Manaus, Amazonas, consisting of plants from the cultivars BRS 1216, BRS 2299, BRS 2314, BRS 2336, BRS 2357, BRS 3137, BRS 3193, BRS3210, BRS 3213, and BRS 3220. The cultivars were characterized according to the profile of bioactive compounds and organic acids. Analysis of variance, mean test, and genetic parameters (genetic, environmental, and phenotypic variance and heritability) were conducted. The heritability of characters was considered from intermediate 63.76% (trigonelline) to high 88.44% (caffeine). Of the compounds studied, trigonelline contents ranged from 0.54 to 0.78 g.100g-1, chlorogenic acids from 3.77 to 5.31 g.100g-1, caffeine from 2.31 to 4.13 g.100g-1, and citric acid from 0.76 to 1.28 g.100g-1. It was observed that there is genetic variability among the cultivars for the compounds studied, and the cultivars can be used in breeding programs for the development of new cultivars.
Análise de compostos bioativos, ácidos orgânicos e parâmetros genéticos de dez cultivares de robustas amazônicos
Keywords: Caffeine; Chlorogenic acids; Coffea canephora; Plant genetics; Trigonelline